Palyno‐morphological diversity of Asteraceous and Poaceous allergenic plant using microscopic techniques in lesser Himalaya‐Pakistan. Issue 6 (30th January 2022) - Anar, Maryam; Ahmad, Mushtaq; Zafar, Sadia; Elnaggar, Ashraf Y.; Zafar, Muhammad; Sultana, Shazia; Tariq, Akash; Anjum, Farida; Hussein, Enas E.; Kiliç, Ömer; Ozdemir, Fethi Ahmet
Abstract: In classification and identification of plant species, palyno morphological character has remain helpful for plant taxonomist. The aim to investigation this study was to identify the characteristic features of Asteraceae and Poaceae family member collected from lower Himalayas of Pakistan. Light microscope and Scanning electron microscope were used for feature study of allergenic pollen. Our study includes 10 species of Asteraceae and Poaceae family. The most dominant shape of pollen was Oblate‐spheroidal, Prolate‐Spheroidal, Prolate and Suboblate shape of pollen. Quantitative character of pollen includes maximum pollen diameter found in Dichanthium annulatum (46.0 μm) and minimum polar axis pollen diameter found in Parthenium hysterophorous (16.0 μm). Similarly highest value of P/E ratio was noted in Cenchrus echinatus (1.05) and smallest value of P/E ratio was observed in Erigeron bonariensis (0.88). Poaceae family member were monoporate. Character feature of exine sculpturing include Microechinate, granulate, echinate, conical base, lacunae Nanogammate, Aerolate‐Scabratre, Verrucate, like variation found in exine of both family member. Highest value of pollen fertility was observed in P. hysterophorous 93%, Similarly maximum value of pollen sterility was noted in E. bonariensis and Brachiaria reptans 24%. This investigation provides the characteristic feature of allergenic pollen species and help to arrange them in define class. Research Highlights: Pollen has affected many people around the world. Using microscopic techniques, morpho‐palynological analysis of Asteraceae and Poaceae families were recognized. LM and SEM study show both qualitative and quantitative character of pollen. Identification of allergenic pollen and microscopic identified character play important role for proper guideline of identification of pollen having allergenic potential. Abstract : Species collected of family Astraceae and Poaceae, that is, (a) Artemisia scopoaria, (b) Erigeron bonariensis, (c) Parthenium hysterophorous, (d) Sonchus asper, (e) Sonchus oleraceus, (f) Brachiaria reptans (g) Cenchrus echinatus, (h) Cymbopogan ceasius (i) Dichanthium annulatum, and (j) Saccharum spontaneum .